Evaluasi Efektivitas Pembelajaran Semi-Adaptif Berbasis Artificial Intelligence Terhadap Motivasi, Pemahaman, dan Kemandirian Belajar Siswa SMP Islam - Fakhrur Razy; Aufatus Syakira Mardhatillah; Liza Efriyanti (Southeast Asian Journal of Islamic Education Management, 2025)
This study aims to evaluate the effectiveness of Artificial Intelligence (AI)-based semi-adaptive learning on students’ motivation, comprehension, and learning independence at SMP Islam Al-Ishlah Bukittinggi. The research employed an evaluative study design using a mixed methods approach, combining descriptive quantitative and qualitative data to obtain a comprehensive understanding of the implementation of AI-based learning. Quantitative data were collected through a 4-point Likert scale questionnaire administered to 28 ninth-grade students of class IX.A using a total sampling technique. Qualitative data were obtained through interviews with teachers and students, as well as classroom observations. Quantitative data were analyzed using descriptive statistics and instrument reliability testing, while qualitative data were analyzed thematically to strengthen and explain the numerical findings. The results indicate that students demonstrated a high level of readiness and understanding of AI use in learning, with an agreement rate of 92%. The use of AI applications was perceived as effective by 84% of students in enhancing learning motivation and comprehension through flexible learning pace and automated feedback. The impact of AI-based semi-adaptive learning on motivation and comprehension was categorized as high, whereas students’ learning independence was at a moderate level, as some students still required teacher clarification. These findings confirm that AI-based semi-adaptive learning effectively improves learning quality; however, its success strongly depends on teacher guidance, infrastructure readiness, digital literacy, and the integration of Islamic educational values.